Answer:
x = 4 and y = -2
Step-by-step explanation:
To solve this system of equations, we can use the substitution method or the elimination method. Let's use the substitution method:
Given equations:
1. y = 2 - x
2. 3x - 2y = 16
We can substitute the expression for Y from the first equation into the second equation:
3x - 4x + 2x = 16
5x - 4 = 16
5x = 20
x = 4
Now that we have found the value of x, we can substitute it back into either of the original equations to find y. Let's use the first equation:
y = 2 - x
y = 2 - 4
y = -2
So, the solution to the system of equations is: x = 4 and y = -2